Trends during 20 years of cuban scientific production on infectious diseases - Salgado Fuentes, Carlos Enrique; Hernandez RodrÃguez, Eglis; Zayas Fundora, Emmanuel (Universidad Médica Pinareña, 2022)
Introduction: the international epidemiological scene is characterized by the co-circulation of several infectious diseases. In this context, bibliometrics needs to use modern technologies and tools that offer updated and reliable information about the behavior of science in the most diverse branches of knowledge. Objective: to characterize the behavior of Cuban scientific production on infectious diseases in SCOPUS. Method: an observational, descriptive and retrospective longitudinal bibliometric study was carried out, in which the data offered by Scimago Journal & Country Rank were used. A search was made of the data offered by this platform on the publications on infectious diseases carried out in Cuba from 2001 to 2020. Results: In the period studied, a total of 1,342 documents were published for an average of 67.1 documents per year. The growth rate in this period was 178.9% with an average annual rate of 8.9%.A total of 20 383 cites were made in the period for an average of cites of 1019,1 cites per year.The total number of self-citations was 3700, the years 2006 (362) and 2007 (358) were the years with the highest number. Conclusions: cuban scientific production on infectious diseases has a marked upward trend, however it is necessary to increase scientific training in these areas in order to improve quality and impact and thus increase the number of citations. Self-citations maintain values higher than those found in other subject areas and a tendency to decrease.